2017
DOI: 10.15761/bem.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic anatomy of the sternum: A micro-CT study to guide the fixation of sternal fractures

Abstract: Background: The rise of manubriosternal joint (MSJ) fractures and lack of literature has spurred an interest in surgical fixation. We hypothesize that locations exist within the sternum that will yield best screw purchase and more rigid fixation of sternal fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As mentioned earlier, the vital role of cortical thickness in bone surgery has been previously demonstrated, and it can thus be considered that cortical thickness affects the surgical procedure and postoperative stability [ 11 , 14 , 15 , 19 , 20 , 27 , 28 ]. Studies have indicated the importance of assessing cortical thickness to determine the optimum anatomical location for fixation [ 15 , 27 32 ]. Placement of the plate and screw over the mandibular body should be performed with caution in order to avoid injury to the IAN canal that runs through the structure.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, the vital role of cortical thickness in bone surgery has been previously demonstrated, and it can thus be considered that cortical thickness affects the surgical procedure and postoperative stability [ 11 , 14 , 15 , 19 , 20 , 27 , 28 ]. Studies have indicated the importance of assessing cortical thickness to determine the optimum anatomical location for fixation [ 15 , 27 32 ]. Placement of the plate and screw over the mandibular body should be performed with caution in order to avoid injury to the IAN canal that runs through the structure.…”
Section: Discussionmentioning
confidence: 99%